SUATU MODEL PENDIDIKAN DENGAN SISTEM BELAJAR MANDIRI (Jurnal TEKNODIK, 2018)
This case study research was focused to find out what, why and how (1) PGMKSBM was implemented; and (2) the diffusion of PGMKSBM was taken. Data collection techniques used were (1) questionnaires; (2) in-depth interviews; and (3) documents and archives analysis. Scope of the study was limited only to the implementation of PGMKSBM in Banten Province. Research findings show that PGMKSBM is an in-service training program aimed to enhance the teacher’ qualification (D-2 or D3) for teachers who are still active teaching but do not has qualification as required, yet. PGMKSBM has some unique characteristics, i.e. (1) it’s in-service training program, not preservice training program; (2) using independent learning system that integrated with the daily teaching practices; (3) applying collaborative action research approach to synergize between theory and daily teaching practices; (4) using authentic assessment technique (portfolio) beside pencil on paper test as learning assessment tools; and (5) use peers and principals as partner and learning resources. Success of PGMKSBM implementation can be showed by some indicators, i.e. (1) quantity of graduated students; (2) improvement of student’ mastery of teaching; (3) teacher performance improvement in school; and (4) improvement on student’ achievement.